Application of entransy theory on structure optimization of serrated fin in plate-fin heat exchanger. (5th June 2020) - Li, Ke; Wen, Jian; Liu, Yuce; Liu, Huaqing; Wang, Simin; Tu, Jiyuan
Highlights: Entransy-dissipation-based thermal resistance is used to evaluate serrated fin. The effects of geometric parameters and Re on fin surface performance are studied. Improved structures of serrated fin based on EDTR objectives are proposed. Optimal results based on EDTR objectives and traditional objectives are compared. Abstract: The effects of geometrical parameters of serrated fin in plate-fin heat exchanger (PFHE) on entransy-dissipation-based thermal resistance (EDTR) caused by heat transfer ( R ht ) and fluid friction ( R ff ) are investigated by design of experiment(DOE) and response surface methodology (RSM) in this paper. The results show that the fin height, fin interrupted length and fin space are positively correlated with R ht, while the fin thickness and PFHE length are negatively correlated with R ht . R ff is far larger than R ht, for about an order of magnitude, and R ff increases almost linearly with the increase of Re when geometric parameters are fixed. R ff increases with fin thickness and PFHE length, and decreases with fin height, fin interrupted length and fin space. Furthermore, Multi-objective Genetic Algorithm (MOGA) is carried out. Compared with the original design, R ht of optimal structure 1 and 2 obtained based on two objectives of minimizing R ff and minimizing R ht reduces by 27.9% and 41.2%, respectively, and R ff reduces by 65.3% and 55.8% respectively. Compared with the optimal results based on traditional objective functions (maximize j and minimize f ), R ht and R ff obtained based on EDTR objective functions reduce by an average of 37.6% and 30.3% respectively, and the JF factor of EDTR optimal results increases by an average of 10.1%.The results show that the optimization results based on EDTR objective functions are better than that based on traditional objective functions for serrated fin in PFHE.